Tarzan ki hamdardi - Mian naveed nasir (Ferozsons (Pvt) Limited ; Lahore)
"Tarzan Ki Hamdardi" is a heartwarming tale that explores themes of compassion and friendship, as Tarzan's unyielding empathy bridges the gap between humans and animals in a jungle filled with challenges and emotional bonds.